A review on pipeline failures, defects in pipelines and their assessment and fatigue life prediction methods. (February 2023) - Vishnuvardhan, S.; Murthy, A. Ramachandra; Choudhary, Abhishek
Abstract: Pipelines are major structures for transporting the liquid or gaseous products and their safe operation is dependent upon the maintenance of structural integrity of the system. Leaks in natural gas pipelines can cause significant harm to people, property, and the environment. Pipelines are damaged mechanically when they subjected to external interferences. In pipes, mechanical defects such as dents, cracks, gouges, and scratches are prevalent. These damages can sometimes occur close to one another, resulting in a single defect in the pipe wall. Individual defects have been demonstrated to be less harmful than compounded defects. A crack in a dent, also known as a dent-crack defect, is one of the pipeline's combined defects. As a result of the damage, the pipeline's capacity may be reduced, and a reliable evaluation of the defect is critical for the pipeline's continued safe operation. At present several assessment methods are available, but there is a need to evaluate these methods against test results. This paper discusses on (i) pipeline failures (ii) defects in pipeline (iii) dents & assessment of dents (iv) cracks (v) dents combined with cracks (vi) monitoring of defects (vii) fatigue life assessment models for the pipes containing mechanical defects. Highlights: Review of causes of pipe line failures, various defects in pipelines and their significance. Monitoring and assessment procedures of dents, cracks and dents combined with cracks in pipelines. Fatigue life assessment models for the pipes containing mechanical defects subjected to internal pressure.